2011
DOI: 10.1007/s00442-011-2146-2
|View full text |Cite
|
Sign up to set email alerts
|

The limit to the distribution of a rainforest marsupial folivore is consistent with the thermal intolerance hypothesis

Abstract: Models of impacts of climate change on species are generally based on correlations between current distributions and climatic variables, rather than a detailed understanding of the mechanisms that actually limit distribution. Many of the vertebrates endemic to rainforests of northeastern Australia are restricted to upland forests and considered to be threatened by climate change. However, for most of these species, the factors controlling their distributions are unknown. We examined the role of thermal intoler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 72 publications
3
40
0
Order By: Relevance
“…Animals restricted to the arboreal environment cannot exploit these thermoregulatory options-however, our study reveals, for the first time, that analogous cool microclimates can be available to these species in the form of cool tree trunks. For koalas, tree-hugging behaviour greatly reduced predicted heat loss requirements, and water savings from this behaviour could be critical for the survival of this species during heat waves when water availability is limited [14], or under high humidity when evaporative cooling is inefficient [2]. Our results are consistent with, and may help explain, previous studies of koalas in more northern populations that found seasonal [18] and weather-dependent differences in tree use, with koalas using non-food trees more frequently during hot days [6,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals restricted to the arboreal environment cannot exploit these thermoregulatory options-however, our study reveals, for the first time, that analogous cool microclimates can be available to these species in the form of cool tree trunks. For koalas, tree-hugging behaviour greatly reduced predicted heat loss requirements, and water savings from this behaviour could be critical for the survival of this species during heat waves when water availability is limited [14], or under high humidity when evaporative cooling is inefficient [2]. Our results are consistent with, and may help explain, previous studies of koalas in more northern populations that found seasonal [18] and weather-dependent differences in tree use, with koalas using non-food trees more frequently during hot days [6,19].…”
Section: Discussionmentioning
confidence: 99%
“…In the wild, however, koalas rarely drink and during dry periods may not have access to free water (e.g. dew on leaves)-potentially restricting this species' capacity to sustain high levels of evaporative cooling; [14]. We therefore predicted that in the wild koalas would use behavioural adjustments to minimize their reliance on evaporative cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Endotherms have high physiological capacities to buffer environmental variations [60], but are not immune to extreme heat waves [38,116,117], which may increase in frequency, intensity and duration as climate warms [118]. For endotherms facing such conditions, perhaps the UCT (figure 2)-or perhaps ambient temperature at the onset of panting-might be useful proxies of risk.…”
Section: Physiological Sensitivity (A) Physiological Traits Dictatingmentioning
confidence: 99%
“…To date, this approach has focussed predominantly on single species [7][8][9][10], limiting inference over the potential impact of climate change on communities. Despite the difficulties of building and parameterising complete mechanistic models, empirical mechanistic studies have provided convincing insights into how particular species and populations are affected by climate, particularly in response to high temperatures (e.g., [11][12][13][14][15][16][17][18][19]). …”
Section: Introductionmentioning
confidence: 99%